Quantum coherence and entanglement partitions for two driven quantum dots inside a coherent micro cavity - Mohamed, Abdel Baset A.; Eleuch, Hichem; Ooi, Chong Heng Raymond (Elsevier, 2019)
We explore the coherence and entanglement of two separated quantum dots placed in an open microcavity. The generated entanglement and coherence depend crucially on the two-exciton decay and the initial coherence intensity. The phenomena of sudden death and sudden birth entanglement are observed. © 2019 Elsevier B.V.